Herbarium specimens as exaptations: New uses for old collections - Heberling, J. Mason; Isaac, Bonnie L. (American journal of botany, 2017)
Herbaria contain an estimated 480 million specimens worldwide accumulated through the efforts of thousands of botanists for over four centuries and counting. These institutions were primarily established to serve as (1) a central resource for taxonomic and floristic studies, including species discovery and description; (2) a comprehensive archive to document biodiversity for medicinal, economic, or scientific purposes; (3) a means to verify species identification; and (4) an accessible repository to formally deposit vouchers to ensure botanical research is both verifiable and repeatable. These conventional functions of herbaria remain essential to botanical research: new species continue to be described, systematic relationships are always subject to revision, nomenclature is routinely updated, and the documentation and study of biodiversity is increasingly important as we enter an anthropogenic era of mass extinction. Here, Heberling and Isaac introduce the analogy of herbarium specimens as "exaptations"--that is, the current use of collections reaches far beyond their originally anticipated uses.